Empirical performance analysis of VCR engine fuelled with karanja oil and various additives using ANOVA technique. Issue 4 (20th March 2020) - Vairavel, M.; Chandrasekaran, M.; Vivek, P.; Vinod Kumar, T.
ABSTRACT: In this present paper, an experimental study is carried out on a single cylinder, four-stroke variable compression ratio (VCR), direct injection diesel engine to analyse the performance characteristics of 20% karanja oil (B20) with diethyl ether, methanol and ethanol as an additives by substituting 5% and 10%, respectively. The engine is operated at the speed of 1500 rpm with VCRs 17 and 18. Analysis of performance parameters such as brake power, indicated power, brake thermal efficiency, mechanical efficiency, specific fuel consumption and indicated thermal efficiency are arrived by the IC engine analysis software which has been coupled with the VCR engine. The outcome data of these blends are to be compared with the ordinary diesel. The results are optimised by using the design of experiments (DOE) method in MINITAB 17.0 software to find out the suitable blend for the engine.